Comparative Observations of Current Flow, Tidal Spectra, and Scattering Strength in and Around Hawaiian Deep-Sea Coral Patches - Parrish, Frank A.; Oliver, Thomas A. (Frontiers in Marine Science, 2020)
Environmental conditions of deep-sea corals were monitored with instruments placed in and adjacent to three Hawaiian deep-sea coral patches dominated by gorgonian octocorals and zoanthid gold coral. Temperature, backscatter, and flow differed among and within the patches and highlighted distinctions in distribution of focus taxa (Hemicorallium laauense, Pleurocorallium secundum, Narella spp., Acanella dispar, Kulamanamana haumeaae). Two of the patches (Barbers Pt., Makapuʻu Pt.) had more than double the sustained mean flow of the third patch (Keahole Pt.), where backscatter levels of the passing water mass showed scattering strengths a third higher, suggesting greater food supply in the water at the Keahole Pt. patch. Further, spectral analysis of flow speed and direction suggests that flow at the first two high-flow sites (Barbers Pt., Makapuʻu Pt.) are dominated by semi-diurnal tidal forcing (flow changing 4x daily, direction 2x daily), while Keahole Pt. patch shows a distinct pattern more typical of diurnal forcing. Of the focus taxa, the two coralliids occupied a similar temperature range but differed in dominance between sites along a flow/scatter gradient, with the “red” coral, Hemicorallium laauense, found at the site with low flow (0.5-4.9 cm/s) and higher scatter (-28 dB) and the “pink” coral, Pleurocorallium secundum, seen at the patch with higher sustained flow (12.6-18.4 cm/s) and lower backscatter (-43 dB). Narella spp. spanned a 10 °C temperature range but were found more frequently at sites with the highest mean flow (18.4-21.7 cm/s). The final two corals, the parasitic zoanthid “gold” coral, Kulamanamana haumeaae, and its most common host, bamboo coral, Acanella dispar, were found at all three sites over a wide temperature range with flow ranging from 2.8 to 18.9 cm/s. The number of gold colonies was negatively correlated with flow even though that relationship was not apparent for the bamboo coral. These patterns were considered in relation to what is known about the life history of deep-sea corals and how they might influence community settlement, growth, and diversity.